2019
DOI: 10.1088/1361-6528/ab1a57
|View full text |Cite
|
Sign up to set email alerts
|

Cooling-field dependence of dipole-induced loop bias

Abstract: In ferromagnet/antiferromagnet bilayers and core/shell nanoparticles, an exchange-bias-like loop bias phenomenon in the ferromagnet is observed solely due to the long-range dipolar interactions between ferromagnet and antiferromagnet. With increasing cooling field, the loop bias field may increase from zero in the bilayers or from a negative value in the core/shell nanoparticles to a positive saturated value, depending on the interfacial dipolar interaction and/or ferromagnetic/antiferromagnetic thickness. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The issue of the cooling field impact on the magnitude and sign of the exchange bias field has been recently raised in a few research papers. However, these works focused on AFM/FM bilayer, 27 spin glass/FM interface, 28 or a system where AFM and FM layers are separated by a paramagnetic material. 29 This paper develops this field of research further by combining two magnetic effects in one study—exchange bias and magnetic exchange spring—to find how they affect the reversal process.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the cooling field impact on the magnitude and sign of the exchange bias field has been recently raised in a few research papers. However, these works focused on AFM/FM bilayer, 27 spin glass/FM interface, 28 or a system where AFM and FM layers are separated by a paramagnetic material. 29 This paper develops this field of research further by combining two magnetic effects in one study—exchange bias and magnetic exchange spring—to find how they affect the reversal process.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, experimentally the EB can be regulated in the real materials CoFe/FeMn/CoFe trilayers depending on thicknesses of the seed CoFe layer and the FeMn layer, while it is independent of the thickness of the target CoFe layer [42]. Actually, the antiferromagnetic layer thickness determines the antiferromagnetic anisotropy energy [20], and thus changing K AF in the literature [42] can be considered approximatively due to change of the antiferromagnetic layer thickness experimentally.…”
Section: Resultsmentioning
confidence: 89%
“…The effects of dipole interactions of ferromagnet and ferromagnet/antiferromagnet interface on the magnetization behaviors have been discussed in our previous papers [20]. Meanwhile, one [21] has suggested that the dipole interaction of antiferromagnet affects only quantitatively rather than qualitatively the symmetry breaking in a thin antiferromagnetic layer.…”
Section: Model and Monte-carlo Simulationmentioning
confidence: 94%
“…The ferromagnet/antiferromagnet interfacial dipolar constant (D IF ) is unknown experimentally, while it is adjustable by changing the spacer thickness [31,32], and according to the reduced magnetic moment set in the antiferromagnetic layer, a smaller value of D IF compared to D FM is used (D IF = 0.4D FM ), which guarantees induction of exchange bias [34]. We employed the image-sum method in the film plane to avoid the drastic effects produced by truncating dipolar interactions [34,38].…”
Section: Model and Monte Carlo Methodsmentioning
confidence: 99%
“…However, when considering largearea ferromagnetic domains, or so-called surplus magnetization, commonly induced at the interface between paramagnetic and antiferromagnetic layers [31], between paramagnetic and ferromagnetic layers [32], or on the surface of nanoparticles [33] as building blocks instead of atoms, the dipolar interaction energy can be orders of magnitude larger. Hu et al [34] used Monte Carlo simulations to reproduce and interpret the cooling -field dependence of the exchange bias field induced by dipolar interactions. Further, they also predicted that a long-range exchange bias field may emerge in the ferromagnet/antiferromagnet core/shell structure.…”
Section: Introductionmentioning
confidence: 99%